Vibration characteristics of a cantilever plate with swept-back leading edge - Heiba, A. E. (College of Aeronautics, Cranfield, 1982)
The paper presents an experimental study of natural frequencies and modes of vibration of uniform cantilever plates. Sixteen planforms are tested by combining aspect ratios of 0.8, 1.2, 1.6 and 2 with leading edge sweep-back angles of 00, 150, 300 and 45°. Experimental values of the natural frequencies for the first six modes are presented for each plate, together with the nodal patterns concerned. The results have been plotted in frequency curves of the same 'family shape'.